Exploring the association between personality traits and colour saturation preference using machine learning - Na Xue; Jinhong Ding (Acta Psychologica)
Both personality traits and colour saturation are associated with emotion; however, how colour saturation preference interacts with different traits and whether this interaction is modulated by object–colour relations remains unclear. In this study, we examined the impact of object–colour relations on colour saturation preference and the relative importance of each personality trait in predicting this preference. Sixty Chinese college students were recruited and registered based on their preferred colour saturation of an object displayed on a computer screen. Random Forest regression analysis in machine learning was applied to ascertain the relative importance of different traits. The results showed that the preferred colour saturation for different objects ranged from high to low: unreal, natural, and artificial. Random Forest regression analysis indicated that personality traits can accurately predict saturation preferences. Specifically, Openness, Extraversion, and Neuroticism are more crucial than Agreeableness and Conscientiousness for objects, while Agreeableness and Openness are the key traits across the three colour hues. Colour saturation preference is also influenced by object–colour association, with each personality trait playing a unique role in this preference due to its relationship with emotions.